THE LITERATURE REVIEW: CHILDHOOD EXPERIENCES OF RELATIONSHIPS AND THE UNEMOTIONAL NATURE OF RELATIONSHIPS IN ADOLESCENTS - huru, guen julia kana; Manafe, Rizky Pradita; Artati, Mardiana (Universitas Nusa Cendana, 2025)
This study aims to evaluate the tendency of Callous Unemotional (CU) traits in early adolescents based on perceptions of parental parenting styles: authoritarian, democratic, and permissive. A comparative cross-sectional design was used. A sample of 236 junior high school students in Pati Regency was selected using cluster random sampling. The research instruments were the Callous Unemotional Traits Scale and the Parental Authority Questionnaire (PAQ). The results showed significant differences in the tendency of CU traits based on parenting style type (p < 0.05). Authoritarian parenting was associated with higher levels of CU traits, while democratic parenting resulted in lower levels. Permissive parenting showed variable results. These results support the theory that tight control and lack of autonomy can hinder children's emotional development. Practical implications highlight the importance of positive parenting styles in preventing the development of CU traits in adolescents.